Tinjauan terhadap Konsep Pengudusan Progresif dalam Perspektif Teologi Reformed - Siahaan, Robert Ridsad (STTI Harvest Semarang, 2024)
Living in holiness is an absolute command that God gives to all God's people. In Reformed theology, the concept of progressive sanctification is very often highlighted and emphasized as a very important part of the Christian's life and relationship with God. This article wants to review the concept of progressive sanctification in the perspective of Reformed theology by highlighting the view of the concept and process that takes place in progressive sanctification and its implications in the practical life of Christians. Sanctification in Reformed theology is seen as a direct act of God in the work of salvation bestowed by God in the work of the cross of Christ and is also a continuous process that Christians must undergo. The method used is Literature review, the author will present the concept of progressive sanctification in the perspective of several reformed theologies such as John Calvin, John Owen, Brakel, Watson and conduct a comparative analysis of the views of David Peterson and Don Payne. The author concludes that sanctification is not a gradual process where Christians become more and more holy and more like Christ. Progressive sanctification is rather seen as a process of transformation and growth in faith towards spiritual maturity in Jesus Christ. In some aspects and in the historical development of Christianity, the author sees that Reformed theology in understanding and practicing the aspect of progressive sanctification has become one of the important benchmarks for Christians in understanding and practicing sanctification itself. AbstrakHidup dalam kekudusan adalah perintah mutlak yang Allah berikan kepada semua umat Allah. Di dalam teologi Reformed konsep mengenai pengudusan progresif sangat sering disoroti dan ditekankan sebagai bagian yang sangat penting dalam kehidupannya orang Kristen dan relasinya dengan Allah. Artikel ini ingin meninjau konsep pengudusan progresif dalam perspektif teologi Reformed dengan menyoroti pandangan terhadap konsep dan proses yang terjadi dalam pengudusan progresif serta implikasinya dalam kehidupan praktis orang Kristen. Pengudusan dalam teologi Reformed dipandang sebagai tindakan langsung dari Allah dalam karya keselamatan yang dianugerahkan Allah di dalam karya salib Kristus dan juga merupakan proses yang terus menerus yang harus dijalani oleh orang Kristen. Metode yang digunakan adalah Literatur review, penulis akan memaparkan konsep pengudusan progresif dalam perspektif dari beberapa teologi reformed seperti John Calvin, John Owen, Brakel, Watson dan melakukan analisis secara komparatif dari pandangan David Peterson dan Don Payne. Penulis menyimpulkan bahwa pengudusan bukanlah suatu proses bertahap dimana orang Kristen menjadi semakin bertambah kudus dan menjadi semakin serupa dengan Kristus. Pengudusan progresif lebih dilihat sebagai suatu proses transformasi dan pertumbuhan iman menuju kedewasaan rohani di dalam Yesus Kristus. Dalam beberapa aspek dan dalam perkembangan sejarah Kekristenan penulis melihat teologi Reformed dalam memahami dan menjalankan aspek pengudusan progresif telah menjadi salah satu tolok ukur penting bagi umat Kristen dalam memahami dan mempraktekkan pengudusan itu sendiri.